A Descriptive Profile of Physical Education Teachers and Programs in Atlantic Canada - Randall, Lynn; Robinson, Daniel; Fletcher, Tim (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
The purpose of this research was to investigate the extent to which quality physical education is currently being taught in Atlantic Canada. We used survey methods to generate descriptive data indicating: (a) the backgrounds of those who teach physical education and (b) what is being taught in physical education. Our findings suggest physical education is taught by a group of mostly-white teachers with varying qualifications, interests, and experiences in teaching the subject. Further, sport experiences tend to dominate the subject matter that students engage with, at the expense of dance and gymnastics. Although some physical education programs could arguably be classified as being of a sound quality according to the national subject association, we contend that more needs to be done to present the subject as a diverse enterprise, both in terms of who teaches and what is taught in physical education.